Pengembangan Instrumen Penilaian Produk Proposal Penelitian Mahasiswa - Sari, Rahmahidayati; Rahma Nengsih, Ayu (Malewa: Journal of Multidisciplinary Educational Research, 2024)
This research was conducted to produce a product, namely a product assessment instrument using a scoring rubric for asess student research proposals. This research was conducted because there was no product assessment instrument for student research proposals. The research method used was using the ADDIE development model. This research was conducted by looking at the feasibility of the assessment instrument created and requesting validation from 3 experts. Revisions are carried out in accordance with suggestions and input from experts. The assessment instrument was declared feasible after revision in accordance with suggestions and input from experts. And the researcher suggests that future researchers carry out dissemination to determine the effectiveness, efficiency and practicability of this product assessment instrument of research proposal.